An Analysis of the Synchronization Between the Military Penal Code and Law Number 1 of 2023 on the Indonesian Criminal Code in the Sentencing System - Hadi, Agustinus Purnomo; Ridwan, Ridwan; Taun, Taun; Santoso, Imam Budi; Hambali, Hambali (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
The enactment of Law Number 1 of 2023 concerning the new Indonesian Criminal Code (KUHP), which replaces the colonial-era Criminal Code, necessitates synchronization and reform of the Indonesian Military Criminal Code. This reform must be examined through the lens of sentencing theories that underpin the vision of the new KUHP. The research aims to identify whether military criminal law aligns with Law Number 1 of 2023, while analyzing and elaborating the required reforms of the military criminal sentencing system. This study employs normative legal research with a global approach as conceptualized by Mulyadi, enabling a clear and comprehensive assessment of sentencing aspects that require synchronization and reform. Findings reveal that the military criminal sentencing system must shift its orientation from retributive to restorative justice. Additionally, reforms are required in several areas, including the focus of sentencing objectives, sentencing guidelines, the scope of additional punishments, and their implementation. The reform of the military criminal code is expected to impact the overall military justice system in Indonesia. In conclusion, synchronization and reform of the sentencing system are necessary to ensure harmonization between lex specialis and lex generalis, thereby preventing overlaps in principles and systems.